2020
DOI: 10.1093/ofid/ofaa028
|View full text |Cite
|
Sign up to set email alerts
|

Two Blood Cultures With Age-Appropriate Volume Enhance Suspected Sepsis Decision-Making

Abstract: Background Multiple blood cultures have been shown to improve pathogen yield and antimicrobial stewardship for adult patients with suspected serious bacterial infection (SBI). For children, the use of multiple blood cultures is less common and volume recommendations are more complicated, often resulting in single cultures with low volume. Methods In 2010, Children’s Hospital Colorado instituted electronic medical record (EMR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…Interventions can correct the weaknesses identified in this study. During sample collection, decision support reminders in the electronic medical record can reduce solitary BCs . Contamination can be reduced by initial specimen diversion, using dedicated phlebotomists, and avoiding blood draws from intravenous catheters .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions can correct the weaknesses identified in this study. During sample collection, decision support reminders in the electronic medical record can reduce solitary BCs . Contamination can be reduced by initial specimen diversion, using dedicated phlebotomists, and avoiding blood draws from intravenous catheters .…”
Section: Discussionmentioning
confidence: 99%
“…During sample collection, decision support reminders in the electronic medical record can reduce solitary BCs. 22 Contamination can be reduced by initial specimen diversion, 23 using dedicated phlebotomists, 24 and avoiding blood draws from intravenous catheters. 25 Blood culture positivity can be increased by increasing the volume of blood collected through education and feedback for personnel, marking the 10-mL point on bottles, 26 and supplying clinical decision tools to avoid BCs in patients at low risk of BSI.…”
Section: Jama Network Open | Infectious Diseasesmentioning
confidence: 99%
“…A recently published study reported that multiple blood cultures with age adjusted volume before antibiotics increased the chance of pathogen isolation in children. 28 Regarding pattern of antibiotic use, reports from Norwegian hospitals show that children use less broad-spectrum antibiotics compared with the entire population. 5,16 This is relevant since detection of pathogen is more difficult if broad-spectrum antibiotics are administrated before blood culture is obtained.…”
Section: Discussionmentioning
confidence: 99%
“…feedback) and computer systems to support doctors to order BC per guidelines. [38][39][40][41][42][43] In our survey, the most common procedures to support or regulate doctors to order BC in their hospitals was presence of local hospital guidelines (33.2%, 352/1,060), followed by case reviews (e.g. grand rounds or morning ward rounds, and BC is often mentioned) (30.8%, 326/1,060), standard order forms to remind ordering BC (29.9%, 317/1,060), stewardship programmes and reviewing BC is included in the programmes (19.5%, 207/1,060), posters (15.4%, 163/1,060) and computer systems to remind ordering BC (10.7%, 113/1,060).…”
Section: Behavioural Regulationmentioning
confidence: 99%